Reboot - Tintera, Amy (HarperTeen, an imprint of HarperCollinsPublishers, 2013)
"Seventeen-year-old Wren rises from the dead as a Reboot and is trained as an elite crime-fighting soldier until she is given an order she refuses to follow"--